Revealing ideology of political speech - Latupeirissa, David Samuel; Laksana, I Ketut Darma; Artawa, Ketut; Sosiowati, I Gusti Ayu Gde (International research journal of management, IT and social sciences, 2019)
In this paper, we reflect on the ideology of political language delivered in political speech. We believe that language in political speech is a tool to spread hidden ideology. The impact of ideology can be positive, or it can also be negative for a nation. Our reflection deals with the revelation of ideology in the political speech text of the Indonesian politician, as well as Indonesian first president, Soekarno. Be based on grounded theory, we examined an important text of political speech that was delivered by Soekarno. The examination applied three main procedures to reveal ideology in text of political speech. The procedures are 1) by analyzing the main rhetorical devices that are used by the politician, 2) by analyzing the construction of the whole text, and 3) by reviewing the context of the situation and the background of the politician. As the results of applying the procedures, it was found that the ideologies of Soekarno’s political speech were ‘unity as the most important value for Indonesia’, revolution as the soul of Indonesia’ and, ‘imperialism as the main enemy of Indonesia’.